STUDI LITERATUR TENTANG EMPATI DALAM KONSELING - Vivie Aryanti; Zulfan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The study aims to identify concepts and theories of empathy in counseling, then factors that affect empathy in counseling based on research results, and ways to increase empathy in counseling based on research results, and discuss research on empathy in counseling based on research findings. Using a literature study method with a qualitative approach, collecting data by collecting previous research results using accredited national and international articles/journals span time from 2014-2021. The journals that were collected were then reselected. and the selected journals would have met the criteria for, accessible by full text, accredited, according to the research topic of empathy in counseling, in English and English. Then the results of the research were analyzed and concluded the formula of the problem. Research results are, conceptually and theoretically, empathy in counseling is the counselor's ability to enter a client's reality, feel a client's feelings, frame strong counseling with the counselor's ability to enter the client's point of view is sometimes considered emphatic understanding, and the counselor's ability is listed as emphatic understanding 1) sincerity, 2) acceptance, 3) the ability to put yourself, the soul, and the feelings of the counselor into the soul, and the feelings of counselor, or if seen in the concept of empathy in counseling then empathy is a skill that describes the quality of the counselor, those skills: 1) respect or positive acceptance, 2) respect and hospitality, or respect and warmth, 3) concreclarity, or clearly and understandably, 4) immediacy or urgency, 5) immediateness, or authenticity displayed by counselors.Key Words: Keywords: empathy; Counseling; behavior